Comparative Effects of Exosomes and Ectosomes Isolated From Adipose-Derived Mesenchymal Stem Cells on Achilles Tendinopathy in a Rat Model. Issue 10 (August 2022) - Xu, Tengjing; Lin, Yunting; Yu, Xinning; Jiang, Guangyao; Wang, Jiajie; Xu, Kaiwang; Fang, Jinghua; Wang, Siheng; Dai, Xuesong
Background: Extracellular vesicles derived from mesenchymal stem cells (MSC-EVs) have gained momentum as a treatment for tendinopathy. Multiple studies have demonstrated significant differences in cargo composition between the 2 subtypes of MSC-EVs (ie, exosomes and ectosomes), which may result in different therapeutic effects. However, the effects of the 2 EV subtypes on tendinopathy have not yet been compared. Purpose: To compare the effects of adipose stem cell–derived exosomes (ASC-Exos) and ectosomes (ASC-Ectos) on Achilles tendinopathy. Study Design: Controlled laboratory study. Methods: Rats were administered collagenase injections to generate a model of Achilles tendinopathy. A week later, 36 rats were randomly assigned to 3 groups. In each group, Achilles tendons were injected with equal volumes of ASC-Exos, ASC-Ectos, or saline (12 legs/group). The healing outcomes were evaluated by magnetic resonance imaging, histology, immunohistochemistry, transmission electron microscopy, and biomechanical testing at 3 and 5 weeks after collagenase injection. Results: At 3 and 5 weeks, the ASC-Exo group had better histological scores ( P = .0036 and P = .0276, respectively), a lower fibril density ( P < .0001 and P = .0310, respectively), and a larger collagen diameter ( P = .0052 and P < .0001, respectively) than the ASC-Ecto group. At 5 weeks, the expression of collagen type 1 and CD206 in the ASC-Exo group was significantly higher than that in the ASC-Ecto group ( P = .0025 and P = .0010, respectively). Regarding biomechanical testing, the ASC-Exo group showed higher failure load ( P = .0005), tensile stress ( P < .0001), and elastic modulus ( P < .0001) than the ASC-Ecto group. Conclusion: ASC-Exos had more beneficial effects on tendon repair than ASC-Ectos in a rat model of Achilles tendinopathy. Clinical Relevance: Administration of ASC-EVs may have the potential to treat Achilles tendinopathy, and delivery of ASC-Exos could provide additional benefits. It is necessary to compare the healing responses caused by different EV subtypes to further understand their effects on tendinopathy and to aid clinical decision making.